Penataan dan Pengembangan Strategi Promosi Pariwisata Melalui Sosial Media di Gunung Telomoyo - Hartanu, Devira Aprillia; Paninggiran, Herman Novry Kristiansen; Izziyana, Wafda Vivid (Tourism Scientific Journal, 2024)
This study aims to assess and analyze the structuring and development of tourism promotion strategies through social media in Mount Telomoyo. The management of Mount Telomoyo tourism has an important role in sustainable development and management of natural and cultural resources. the reason for structuring tourism is for Economic Development. Tourism can be one of the significant sectors of the economy. With a good arrangement, tourism can create jobs, increase community income, and contribute to the economic growth of a region. The methods used in this study are qualitative, data collection, and analysis techniques conducted through observation, interviews, and literature. The research results show that the strategy and promotion aspects of Mount Telomoyo tourism through social media are very important in providing information to tourists to make decisions to visit Mount Telomoyo.